"On the Recovery Journey:" An Integrative Review of the Needs of Burn Patients From Immediate Pre‐Discharge to Post‐Discharge Period Using the Omaha System. Issue 4 (23rd May 2020) - Bayuo, Jonathan; Wong, Frances Kam Yuet; Agyei, Frank Bediako
Abstract: Background: To establish a conceptual understanding of the needs of burn patients, the specific research question asked is: "What are the needs of burn patients from 1‐week pre‐discharge to the post‐discharge period?" Methods: Whittemore and Knafl's integrative review approach was used to answer the review question. The databases searched were the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Embase, and Scopus. Thirty‐two primary studies were retained at the end of the screening process. Directed content analysis was undertaken, with the Omaha system as an organizing framework. Results: Recovery after burns is not a linear process, but an intricate one filled with varied needs in the physiological (pain, skin, neuro‐musculo‐skeletal, and infection), psychosocial (social contact, role changes, spirituality, grief, mental health, and sexuality), health‐related behavior (nutrition, sleep and rest patterns, and physical activity), and environmental (income) domains of the Omaha system. The nature and intensity of these needs change over time, suggesting that recovery for the burn patient is an ongoing process. Conclusions: Several needs exist from 1 week before discharge to the post‐discharge period. The mutual relationship and evolving nature of these needs create an avenue for a flexible, regular, holistic transitional program, similar to the support offered to persons living with chronic conditions. Clinical Relevance: Hospital discharge does not imply an end to the recovery of burn patients, and burn survivors still require holistic care even after discharge. The review shows the applicability of the Omaha system in exploring and classifying the needs of burn survivors and situates nursing at the core of such a program. It is possible that a nurse‐led program of care needs to be considered.